AN IMPROVED METHOD OF HIERARCHIC ANALYSIS FOR CHOOSING OPTIMAL INFORMATION PROTECTION SYSTEM IN COMPUTER NETWORKS - Kuzemko, Sergey; Melnychuk, Volodymyr (Scientific Works of Vinnytsia National Technical University, 2015)
An improved hierarchic analysis method, based on the interval estimate of the preferences of criteria and alternatives, is proposed and investigated. REFERENCES 1. Домарев В. В. Безопасность информационных технологий. Методология создания систем защиты / В. В. Домарев – К.: ООО "ТИД "ДС", 2002. – 688 с. 2. Титоренко Г. А. Информационные технологии управления: учебное пособие для вузов / под ред. проф. Г. А. Титоренко. – 2-е изд., доп. – М.: ЮНИТИ-ДАНА, 2003. – 439 с. 3. Курчиков Л. Н. Неопределенность и определенность / Л. Н. Курчиков – М., 1972. – 432 с. 4. Таха Хемди Введение в исследование операций / Таха Хемди – [7-е изд.]. Пер. с англ. – М.: Вильямс, 2005. – 902 с. 5. Аленфельд Г. Введение в интервальные вычисления / Г. Аленфельд, Ю. Херцбергер – М: Мир, 1987, – 360 с.